IMPLEMENTATION OF STUDENT LEADERSHIP DEVELOPMENT IN THE KETARUNAAN EDUCATION SYSTEM AT AVIATION VOCATIONAL SCHOOLS - Muhammad Shofyan Fauzi (Program Studi Doktor Ilmu Administrasi, FISIP, Universitas 17 Agustus 1945 Surabaya, 2023)
Education in schools that have a cadet education system is different from schools in general, cadet education is a system for instilling character and forming a good personality in children by exemplary, direction, and guidance. This study used a qualitative approach with the research subjects being vice principals, vice principals of public relations, deputy heads of quality management, deputy heads of student affairs, ambal coaches, curriculum teachers, English teachers, and students. The object of research is the implementation of student leadership development which focuses on implementation, constraints, and efforts made by schools in the cadet education system. The research which took place at Aviation Vocational High School used interview, observation, and documentation data collection techniques. The results of the research: (1) The implementation of student leadership development in Aviation Vocational Schools is carried out through the concept of the School of Leadership. School programs that support School of Leadership are internalized in teaching and learning activities, extracurriculars and events. Socialization of the School of Leadership is carried out through print, electronic, social media, and open houses. Infrastructure facilities in the implementation of the School of Leadership are not specifically provided. Funding related to the School of Leadership comes from schools but is still limited. Schools do not yet have experts who are experts in the field of leadership. (2) Supporting factors include. (3) The efforts made by the school are